Ecstasy in the classroom : trance, self, and the academic profession in medieval Paris - Even-Ezra, Ayelet (Fordham series in medieval studies., 2019)
This book analyzes the early thirteenth century theological discourse about Paul's rapture and other modes of cognizing God. It reconstructs the perceptions of transformation and self they imply, and demonstrate their role in establishing the peculiar professional identity of scholastic theologians compared with other seers of God.